Bacterial urinary tract infection among adult renal transplant recipients at St. Paul’s hospital millennium medical college, Addis Ababa, Ethiopia - Teklehaimanot Kiros; Daniel Asrat; Zeleke Ayenew; Estifanos Tsige (BMC Nephrology, 2019)
Abstract Background Despite significant advances in surgical techniques, immunosuppression protocols, follow up periods and antimicrobial stewardship in modern medicine; post-renal transplantation urinary tract infection remained a major public health problem globally. This multiple serious squeals includes asymptomatic bacteriuria, cystitis and pyelonephritis. Among these, the bacterial origin of infection complications accounts for the most significant clinical, socio-economic impacts in many countries of the world. Therefore, the aim of the study was to investigate the prevalence of bacterial isolates that cause urinary tract infections, assess antibiotic susceptibility pattern among symptomatic and asymptomatic renal transplant recipients attending at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia. Methods A hospital-based cross-sectional study was conducted from December 2017 to August 2018 among 74 renal transplant recipients St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia. A first morning voided clean-catch mid-stream urine specimens were collected and 0.001 ml inoculated onto blood and MacConkey agar plates following the standard bacteriological protocols. It was incubated aerobically at 35–37 °C for 24–48 h. Cultural characteristics and series of biochemical tests were used for the identification of isolates to species level based on the standard bacteriological protocols. Results A hospital-based cross-sectional study has shown that significant bacteriuria was found in 11/74 (14.9, 95% CI =8.2–24.7) patients. The prevalence among females 6/32 (18.75%) was higher among males 5/42 (11.9%) without significant association (COR = 2.09, 95% CI = 1.04–8.45, P = 0.253). Urinary tract infection was higher in the age group of 35–49 years old (19.3%). Age was statistically significant and stronger independent associated risk factor with crude odds ratio = 3.67, 95% CI = 2.89–20.07 and P = 0.003, respectively. The most prevalent bacteria isolates were Escherichia coli 2(18.2%), Staphylococcus aureus 2(18.2%), Acinetobacter spp. 2(18.2%), Enterococcus spp. 2(18.2%), Coagulase-negative Staphylococci 2(18.2%) followed by Porteus mirabilis 1(9.1%). The majority (80%) of Gram-negative bacteria were resistant to ciprofloxacin, chloramphenicol, and trimethoprim/sulfamethoxazole. Simultaneously, the multidrug-resistant bacterial isolates accounts for 82% among tested kidney allograft recipients. Conclusions In conclusion, the overall prevalence of urinary tract infection in the study participants was relatively low with a prevalence of 14.9%. Majority of the study participants were asymptomatic and a higher percentage of females were involved. The multidrug-resistant bacterial isolates in the present study account for 82%.